Permanent teeth loss: A 5-year retrospective analysis of the patterns and indications of intra-alveolar exodontia in Najran, Kingdom of Saudi Arabia - Ramat Oyebunmi Braimah; Dawood Ali-Alsuliman; Harit Kanwar Sharma; Abdulrazaq O Taiwo; Adebayo Aremu Ibikunle; Yahyah Alsalah; Reham Makrami; Abdullah S Alwalah; Mohammed S Alajam; Abdullrahman Saeed Alalharith (Wolters Kluwer Medknow Publications, 2022)
Introduction: Tooth loss is a worldwide public health concern of huge proportion. Problems associated with permanent tooth loss are enormous. Aim: This study aims to investigate the major reasons and patterns of permanent tooth extraction in a government referral dental center. Materials and Methods: This retrospective study was conducted on patients who had intra-alveolar extraction of teeth in our facility between January 2016 and December 2020. Sociodemographic data and type of tooth extracted were recorded. Reasons for extraction were classified into the following: caries, failed root canal treatment, failed restoration, periodontitis, prosthodontic, orthodontic, trauma, and over-eruption. Data were stored and analyzed with SPSS for MOS, Version 20.0. Results and Discussion: A total of 8065 (3248, 0.3%) males and 4817 (59.3%, females) patients presented for teeth extraction during the study period with 11,746 extractions done, giving an average of 1.5 extractions per individual. The age range of 11-102 years with a mean (±standard deviation) of 36.0 (16.6) was observed. The majority of the patients were in the age groups of 21-30 years (1992 (24.7%), then 31-40 years (1773 (22.0%). Caries and its sequelae accounted for the main reasons for tooth mortality. In the mandible, a total of 5321 (45.3%), while in the maxilla, a total of 6425 (54.7%) teeth were extracted. Molars were the most extracted tooth in both jaws (3485 (29.7%)) Conclusions: The current study found that dental caries, and its sequelae, was the main reason for tooth extraction in a Saudi subpopulation, Najran. Molars were the most commonly extracted teeth.